Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(1,\\ a,=4\left(x-2\right)^2+y\left(x-2\right)=\left(4x-8+y\right)\left(x-2\right)\\ b,=3a^2\left(x-y\right)+ab\left(x-y\right)=a\left(3a+b\right)\left(x-y\right)\\ 2,\\ a,=\left(x-y\right)\left[x\left(x-y\right)^2-y-y^2\right]\\ =\left(x-y\right)\left(x^3-2x^2y+xy^2-y-y^2\right)\\ b,=2ax^2\left(x+3\right)+6a\left(x+3\right)\\ =2a\left(x^2+3\right)\left(x+3\right)\\ 3,\\ a,=xy\left(x-y\right)-3\left(x-y\right)=\left(xy-3\right)\left(x-y\right)\\ b,Sửa:3ax^2+3bx^2+ax+bx+5a+5b\\ =3x^2\left(a+b\right)+x\left(a+b\right)+5\left(a+b\right)\\ =\left(3x^2+x+5\right)\left(a+b\right)\\ 4,\\ A=\left(b+3\right)\left(a-b\right)\\ A=\left(1997+3\right)\left(2003-1997\right)=2000\cdot6=12000\\ 5,\\ a,\Leftrightarrow\left(x-2017\right)\left(8x-2\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=2017\\x=\dfrac{1}{4}\end{matrix}\right.\\ b,\Leftrightarrow\left(x-1\right)\left(x^2-16\right)=0\Leftrightarrow\left[{}\begin{matrix}x=1\\x=4\\x=-4\end{matrix}\right.\)
x(x-4)(x-1)(x+3)+36=[x(x-1)][(x-4)(x+3)]+36
\(=\left(x^2-x\right)\left(x^2-x-12\right)+36\)
Đặt \(t=x^2-x-6\)ta có:
(t+6)(t-6)+36
=t^2 -36 +36
=t^2=....
\(x\left(x-4\right)\left(x-1\right)\left(x+3\right)+36\)
\(=x^4-2x^3-11x^2+12x+36\)
\(=x^4-\left(6x^3-4x^2\right)+\left(9x^2-24x^2+4x^2\right)+\left(36x-24x\right)+36\)
\(=x^4-6x^3+9x^2+4x^3-24x^2+36x+4x^2-24x+36\)
\(=x^2\left(x^2-6x+9\right)+4x\left(x^2-6x+9\right)+4\left(x^2-6x+9\right)\)
\(=\left(x^2-6x+9\right)\left(x^2+4x+4\right)\)
\(=\left(x-3\right)^2\left(x+2\right)^2\)
Xong!
\(\left(x+2\right)\left(x-1\right)+3.\left(x-1\right)=\left[\left(x+2\right)+3\right].\left(x-1\right)\)
\(=\left(x+5\right).\left(x-1\right)\)
\(1,=x\left(x^2-2x+1-y^2\right)=x\left[\left(x-1\right)^2-y^2\right]=x\left(x-y-1\right)\left(x+y-1\right)\\ 2,=\left(x+y\right)^3\\ 3,=\left(2y-z\right)\left(4x+7y\right)\\ 4,=\left(x+2\right)^2\\ 5,Sửa:x\left(x-2\right)-x+2=0\\ \Leftrightarrow\left(x-2\right)\left(x-1\right)=0\Leftrightarrow\left[{}\begin{matrix}x=1\\x=2\end{matrix}\right.\)
\(x\left(x+1\right)\left(x+2\right)\left(x+3\right)+1\)
\(=\left[x\left(x+3\right)\right]\left[\left(x+1\right)\left(x+2\right)\right]+1\)
\(=\left(x^2+3x\right)\left(x^2+3x+2\right)+1\)
Đặt \(x^2+3x=t\) ta có :
\(\left(x^2+3x\right)\left(x^2+3x+2\right)+1=t\left(t+2\right)+1=t^2+2t+1=\left(t+1\right)^2\)
\(=\left(x^2+3x+1\right)^2\)
Vậy \(x\left(x+1\right)\left(x+2\right)\left(x+3\right)+1\) phân tích thành nhân tử là \(\left(x^2+3x+1\right)^2\)
x [x - 1] + x [ x + 3 ]
= x [ x - 1 + x + 3 ]
= x [ 2 x + 2 ]
= 2 x [ x + 2 ]
`x(x-1)+x(x+3)=x(x-1+x+3)=x(2x+2)=2x(x+1)`